Influence of PVA on wettability alteration of carbonate rocks: the role of different ions - Abdulla, Rafal S.; Hussein, Hussein Q.; Jalil, Rana R. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The petroleum industry faces a significant problem in enhanced oil recovery (EOR) from carbonate reservoirs because of their mostly oil-wet character, which restricts hydrocarbon extraction. To better understand how surfactant-polymer techniques can enhance oil recovery, this study investigates the effectiveness of polyvinyl alcohol (PVA) as a stand-alone agent and the function of ionically modified smart water on carbonate properties. The study focuses on its effect on critical parameters essential for effective oil displacement and recovery, such as wettability alteration, interfacial tension, and surface tension (ST) using different brines (smart water). The ability of the polymer PVA to lower interfacial and surface tension was investigated. PVA decreased surface tension in brine to 44 mN/m, although smart water solutions showed more noteworthy outcomes. When PVA was added to smart water with a 1:1 Mg²⁺/SO4²⁻ ratio, the lowest ST (29 mN/m) and IFT (11.8 mN/m) values were observed. The hydrophilic properties of PVA and its ionic interaction with Mg²⁺ were key factors in encouraging water adsorption on the surface of the carbonate rock. The contact angle was getting closer to zero, indicating that this interaction resulted in a full transition to a water-wet condition. Enhancing the oil displacement process in carbonate reservoirs—generally refractory to recovery—requires this complete transition to water-wet conditions. This full shift to water-wet conditions is vital for enhancing the oil displacement process in carbonate reservoirs, which are typically resistant to recovery due to their oil-wet surfaces.